Klinefelter Syndrome With Leg Ulcers - Narendra G; Sasikala K; Karthikeyan D P; Srinivas C R (Wolters Kluwer Medknow Publications, 1999)
Leg ulcers are frequently caused by venous insufficiency, arterial insufficiency, neuropathy, or a combination of these factors. Klinefelter syndrome in association with chronic leg ulcers have been reported earlier. We report a case of Klinefelter syndrome with non- healing ulcer. The diagnosis of the Klinefelter syndrome was confirmed by karyotyping.